A Review on Research and Application of AI-Based Image Analysis in the Field of Computer Vision - Pan Wu; Xiaoqiang He; Wenhao Dai; Jingwei Zhou; Yutong Shang; Yourong Fan; Tao Hu (IEEE Access)
The rapid development of artificial intelligence has significantly advanced the field of computer vision, particularly in image analysis and understanding. This paper provides a comprehensive review of the current state of the field, key technologies, and their applications across various real-world scenarios. It delves into the value of image analysis in critical areas such as personalized art, healthcare and medical image analysis, security monitoring and recognition technology, autonomous driving and traffic management, as well as industrial automation and quality control. This paper not only highlights the challenges and limitations, including dataset constraints, algorithm generalization, real-time computational costs, and privacy and ethical concerns, but also offers a forward-looking analysis of development trends such as interdisciplinary integration, weakly supervised and unsupervised learning, algorithm optimization and hardware advancements, and the protection of personal privacy and information. These insights provide a profound perspective on the future trajectory of computer vision and AI-driven image analysis.